2020
DOI: 10.1007/s11356-020-08937-4
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate toxicity: updates of malathion potential toxic effects in mammals and potential treatments

Abstract: Organophosphorus insecticides toxicity is still considered a major global health problem. Malathion is one of the most commonly used organophosphates nowadays, as being considered to possess relatively low toxicity compared with other organophosphates. However, widespread use may lead to excessive exposure from multiple sources. Mechanisms of MAL toxicity include inhibition of acetylcholinesterase enzyme, change of oxidants/antioxidants balance, DNA damage, and facilitation of apoptotic cell damage. Exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 221 publications
(361 reference statements)
3
53
0
1
Order By: Relevance
“…Our results revealed that MAL-treatment induced a signi cant increase in the level of IL-β in the testis, kidney, and lung tissues, while blood, liver, kidney, and heart IL-β level reduced. Experimental studies proved that sub-chronic MAL-induced tissue damage resulted in stimulate in ammatory cytokines releasing in hepatocytes, such as IL-1β (Badr 2020). Moreover, Ince et al(2017) reported an increased IL-1 beta expression MAL-induced toxicity rat model.…”
Section: Discussionmentioning
confidence: 97%
“…Our results revealed that MAL-treatment induced a signi cant increase in the level of IL-β in the testis, kidney, and lung tissues, while blood, liver, kidney, and heart IL-β level reduced. Experimental studies proved that sub-chronic MAL-induced tissue damage resulted in stimulate in ammatory cytokines releasing in hepatocytes, such as IL-1β (Badr 2020). Moreover, Ince et al(2017) reported an increased IL-1 beta expression MAL-induced toxicity rat model.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies in humans have suggested pesticides, including malathion, are linked to nephrotoxicity [ 30 ]. An El Salvadoran study did not find a relationship between “ever use” of 2,4-D, organophosphates, and pyrethroids and reduced kidney function among sugarcane workers after harvest season based on self-reported exposure [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…While little is known about the nephrotoxic pathological pathways of pesticides with most evidence derived from animal studies [ 29 ], the pathological pathway will depend on the class of toxin involved. Organophosphates have been implicated in nephrotoxic activity in animals via oxidative stress (reduced glutathione metabolism) [ 30 ] and in porcine cell culture via oxidative stress at the tubular level [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in humans have suggested pesticides, including Malathion are linked to nephrotoxicity (Badr 2020). An El Salvadoran study did not nd a relationship between "ever use" of 2,4-D, organophosphates and pyrethroids and reduced kidney function among sugarcane workers after harvest season, based on self-reported exposure (Garcia-Trabanino et al 2015).…”
Section: Pesticide Exposures With Kidney Function Loss and Ckdumentioning
confidence: 99%